Volatile N-nitrosamines in meat products: Potential precursors, influence of processing, and mitigation strategies. Issue 13 (2nd September 2017) - De Mey, Eveline; De Maere, Hannelore; Paelinck, Hubert; Fraeye, Ilse
ABSTRACT: Meat products can be contaminated with carcinogenic N -nitrosamines, which is ascribed to the reaction between a nitrosating agent, originating from nitrite or smoke, and a secondary amine, derived from protein and lipid degradation. Although in model systems it is demonstrated that many amine containing compounds can be converted to N -nitrosamines, the yield is dependent of reaction conditions (e.g., low pH and high temperature). In this article, the influence of the composition of the meat products (e.g., pH, aw, spices) and processing (e.g., ageing, ripening, fermentation, smoking, heat treatment and storage) on the presence and availability of the amine precursors and the N -nitrosamine formation mechanism is discussed. In addition, this article explores the current N -nitrosamine mitigation strategies in order to obtain healthier and more natural meat products.